Current performance standard of circular product design: A systematic literature review - Sri Indrawati; Subagyo Subagyo; Agus Darmawan (OPSI, 2026)
The rising number of green customers has encouraged industries to assess product consequences. As a result, there has been an alignment of product development focus with regards to circular economy concepts. Consequently, several methods and tools have been developed, and thus new performance standards were introduced for product development. Nevertheless, there still exist deficiencies in industry-wide acceptance and adoption within these standards. The objective of the study aims at examining and optimizing existing standards on Circular Product Design. A systematic literature review method will be adopted with three phases: identifying research on Circular Product Design using Preferred Reporting Items for Systematic Reviews and Meta-Analyses, developing approaches on designs, and examining standards on design performance. The result shows that there are seven prevailing approaches on designs for Circular Product Design. Moreover, this study contributes an a structured classification of CPD approaches and performance standards, thus dealing with the problem of fragmented knowledge and and serves as a basis for further frameworks and research on circular product performance.